Personal COVID-19 hygiene kit for kids (COHYKS) / Tuan Noorkorina T.K. ... [et al.] - T.K, Tuan Noorkorina; M.F., Nik Ainul Mardhiah; T.M.N, Tengku Nur Aina Qistina; R., Kadir; S.S., Mohd Noor; A., Jaafar; N.H.A., Rahman; F.C., Hassan; N., Murshid; S.A., Zulkefli; A., Abdullah; N.R., Mustafa; et al. (Universiti Teknologi MARA, Perak, 2020)
Children always have bad hygiene. Since most of them never practise proper handwashing, they are at risk of being infected by bacteria, fungi, and viruses, especially COVID-19. Concerning this issue, we develop a Personal COVID-19 Hygiene Kit for Kids, known as 'COHYKS'. COHYKS focuses on supplying children with a complete set of interactive hygiene kits, such as hand wash, hand sanitiser, mask, thermometer, and tissue paper, aiming at inculcating good health behaviours among school children. Compared to other marketed products, COHYKS is supplied with flashcards, comprising six steps of handwashing and Covid-19 warning signs. COHYKS is packed in a small travelling bag, illustrating Covid-19 prevention and precaution as well as the QR code for video of handwashing steps for kids. A community programme concerning hygiene and handwashing awareness was conducted at Sekolah Rendah Islam Al-Qari, Kubang Kerian, Kelantan. Other than lecture, exhibition, and demonstration of hand washing and hand scrubbing, the students were given hygiene kits including hand wash to practise handwashing on their own. It was found that most of the students were aware of hand hygiene and started to practise hand hygiene after the programme.